2010
DOI: 10.1371/journal.pone.0010100
|View full text |Cite
|
Sign up to set email alerts
|

Thirty-One Novel Biomarkers as Predictors for Clinically Incident Diabetes

Abstract: BackgroundThe prevalence of diabetes is increasing in all industrialized countries and its prevention has become a public health priority. However, the predictors of diabetes risk are insufficiently understood. We evaluated, whether 31 novel biomarkers could help to predict the risk of incident diabetes.Methods and FindingsThe biomarkers were evaluated primarily in the FINRISK97 cohort (n = 7,827; 417 cases of clinically incident diabetes during the follow-up). The findings were replicated in the Health 2000 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
169
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 155 publications
(184 citation statements)
references
References 35 publications
12
169
1
2
Order By: Relevance
“…The Malmö Diet and Cancer (MDC) study showed that copeptin, independently of a wide range of clinical risk factors, predicts the risk of type 2 diabetes in the general population [6]. However, the FINRISK97 study could not find an independent association [32]. The fact that we found a stronger association between copeptin and the risk of type 2 diabetes in women than in men might partly be explained by differences in population characteristics compared with other studies.…”
Section: Discussioncontrasting
confidence: 77%
See 4 more Smart Citations
“…The Malmö Diet and Cancer (MDC) study showed that copeptin, independently of a wide range of clinical risk factors, predicts the risk of type 2 diabetes in the general population [6]. However, the FINRISK97 study could not find an independent association [32]. The fact that we found a stronger association between copeptin and the risk of type 2 diabetes in women than in men might partly be explained by differences in population characteristics compared with other studies.…”
Section: Discussioncontrasting
confidence: 77%
“…The FINRISK97 study from a cohort of 7,827 participants with 417 incident cases included similar numbers of women and men [32]. In the FINRISK97 study, a higher but non-significant risk of type 2 diabetes per one SD increase in copeptin was found in the total and sex-stratified population [32]. In this latter study, the range of copeptin levels was smaller than in the MDC study and our study, for both women and men.…”
Section: Discussionsupporting
confidence: 42%
See 3 more Smart Citations